عزل وتصنيف النوعين الجرثوميين Pseudomonas pachastrellae Micrococcus brunensis من تربة ملوثة بمركبات نفطية - ناصر, أميمة (Latakia University Journal -Biological Sciences Series, 2016)
عُزل نوعان من الجراثيم من ترب ملوثة بمركبات نفطية, تم تمييز العزلتين الجرثوميتين ببعض الخصائص اعتماداً على تلوينها بطريقة غرام, وبعض الخصائص الشكلية والكيميائية الحيوية. بينت النتائج عزل نوعان من الجراثيم, النوع الأول عصوي قصير سالب صبغة غرام, تميز بتفاعل سلبي تجاه اختباري اليوريا والنترات, وتفاعل إيجابي بالنسبة لاختبار سكر الغلوكوز فقط, والنوع الثاني من جراثيم المكورات العنقودية موجب صبغة غرام, تميز بتفاعل سلبي تجاه اختباري الجلاتين واستعمال السترات, كما أعطى تفاعل سلبي بالنسبة لاختبار سكر المالتوز والمانيتول, واستناداً إلى تصنيف بيرجي, وخلال فترة حضانة استمرت (48-72) ساعة, وعند درجة حرارة (37) درجة مئوية.والجراثيم المعزولة هي نوعان: الأول Pseudomonas pachastrellae , والثاني Micrococcus brunensis. Two bacterial species were isolated from petroleum hydrocarbon-contaminated soil. The isolates were characterized based on their gram reaction characteristics, morphological and biochemical properties.The results showed two bacteria isolated the first isolated: gram negative short rod, urease and nitrate reduction test showed a positive result , and glucose test showed positive result. And the second isolated: gram positive cocci, gelatin and Citrate utilization test showed a positive result , and maltose, mannitol test showed negative result. They were then incubated at (37) ° C for (48- 72) hours.This is based on comparison of results with Bergey Manual of systematic bacteriology.The isolates were identified to be: Pseudomonas pachastrellae (X1) Micrococcus brunensis (X2).